26=25-3x

Simple and best practice solution for 26=25-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26=25-3x equation:



26=25-3x
We move all terms to the left:
26-(25-3x)=0
We add all the numbers together, and all the variables
-(-3x+25)+26=0
We get rid of parentheses
3x-25+26=0
We add all the numbers together, and all the variables
3x+1=0
We move all terms containing x to the left, all other terms to the right
3x=-1
x=-1/3
x=-1/3

See similar equations:

| x-0.2x=882 | | 2b(-9)=0 | | 2x+20+x=110 | | |-3x+12|=15 | | 3x+12=2- | | -34=v+42-6v | | 1/2(y-3)=1/4(y+1) | | 47-10x=19+4x | | 3x-5(x-6)=-2(10-x)-10 | | 2x+.5x=180 | | x-0.2x=4520 | | 3+20x=19x+9 | | (8x+7)(x-3)=0 | | -2-r/3=5 | | X+11=4x= | | 150-100+43650=45675-175m | | 5h=4=7h=24 | | 5t-22=33 | | 15x–7=8x+2 | | g(25)=24(-14-39) | | 3x+15=-32 | | -x8=96 | | 2i-16=12(i+8) | | t+19=20 | | 7x^2-242x+663=0 | | 12x-9=8x+2 | | 24=(x-39) | | 0.15+0.05(10-x)=0.10(10) | | 2-3s=-7.72 | | x=310 | | 3.7+2h=5.7 | | 3x-5(x-2)=-4+3-1 |

Equations solver categories